PEMANFAATAN ARTIFICIAL INTELLIGENCE DALAM EVOLUSI CRYPTOCURRENCY: KAJIAN SISTEMATIS ATAS PELUANG, RISIKO, DAN TANTANGAN REGULASI - Omasrianto; Yusuf, Muh. Fathir Maulid (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The integration of artificial intelligence (AI) into the cryptocurrency ecosystem has emerged as a transformative phenomenon that promises enhanced efficiency, heightened security, and innovation across digital financial systems, while simultaneously presenting significant ethical and regulatory challenges. This study aims to identify and synthesize recent scholarly findings concerning the application of AI in the realm of cryptocurrency by examining strategic opportunities, inherent risks, and the regulatory complexities that arise from the convergence of these two technologies. Employing a Systematic Literature Review (SLR) approach based on the PRISMA 2020 protocol, this research analyzed 36 academic articles published between 2020 and 2025, sourced from leading databases. The review reveals four core thematic categories: AI-driven market prediction and automated trading, the use of AI in fraud detection systems, identification of ethical risks and algorithmic bias, and the evolving policy responses to AI–crypto integration. This article offers a conceptual contribution by integrating the Technology Acceptance Model, Diffusion of Innovations, and FinTech Governance frameworks to provide a holistic understanding of the adoption and governance dynamics of these technologies. The findings are expected to serve as a strategic reference for policymakers, technology developers, and the academic community in formulating adaptive, ethical, and sustainable digital governance strategies..